Alcohol use by drug addicts during the treatment and follow-up - Sanabria Carretero, Manuel (Pontificia Universidad Católica del Perú, 2002)
This study is about the use of alcohol and its influence during the recuperation of drug addict patients undergoing treatment. Levels of the use of illegal drugs and alcohol were compared before, during and after the treatment of 82 patients assessed over a one-and-a-half year follow-up study. The results show that after the intervention there is an increase of alcohol use by 50% of the addicts. The 10-13% exhibit excessive levels. The higher alcohol use coincide withthe end of the treatment. This tendency changes later (18 months) into similar levels as the initialones. These results do not allow to consider the aforementioned increase as a confirmationof the substitution hypothesis, that is the alcohol use-redirection towards other more socially tolerated substances.